Analysis of The Effect of Life Expectancy (AHH) and Per Capita Expenditure on The Human Development Index (HDI) in Central Sulawesi Province in 2019 - Sakinah, Nur; Ihlasia, Nurmasyita; Nurfitra; Sagap, Marni; Rachman, Rohis; Handayani, Lilies (Parameter: Journal of Statistics, 2022)
A measurement of a nation's human resource condition is the human development index (HDI). The three components of the human development index are living standards, often known as economics, and health. In Central Sulawesi Province in 2019, this study seeks to ascertain the impact of life expectancy (AHH) and per capita spending on the human development index (HDI). Secondary data from the Central Statistics Agency (BPS) of Central Sulawesi Province, corroborated by additional sources, was used in this study. The multiple linear regression analysis methods were the analysis technique used in this study.The findings demonstrated a positive and significant impact of partially variable Life Expectancy (AHH) and per capita spending variables on the Human Development Index (HDI). The Human Development Index (HDI) in Central Sulawesi Province is thereafter significantly impacted by the combination of the two independent factors in 2019.